Arctic shipping : future polar express seaways? : shipowners’ opinion - Lasserre, Frédéric; Pelletier, Sébastien (Jefferson Law Book Co., 2016)
Since about 1995, climate change has begun to mark Arctic region. The first and strongest signs of global-scale climate change exist in the high latitudes of the planet. The Earth is indeed facing what is now known as Global Warming. With the world economy continuing to grow rapidly, driven in particular by fast economic take-off in countries such as China, Brazil and India, these climate changes are likely to rush the Arctic's development and usher in a new phase of globalization. Meanwhile, demand for energy (oil and gas) and raw materials (iron, nickel, zinc, etc.) is increasing. As the reserves of some important resources such as oil run out, and assuming that diversification of supply sources has been seen as the key to energy security, energy companies scour the globe in search of promising new fields, and now in inhospitable regions which until recently aroused little interest given the importance of costs of such exploration projects.